Protection and Guidance of Downstream Moving Fish with Electrified Horizontal Bar Rack Bypass Systems - Meister, Julian; id_orcid:0 000-0002-2715-6780; Moldenhauer-Roth, Anita; id_orcid:0 000-0002-2902-4028; Beck, Claudia; id_orcid:0 000-0001-9021-1378; Selz, Oliver M.; Peter, Armin; Albayrak, Ismail; id_orcid:0 000-0002-4613-6726; Boes, Robert; id_orcid:0 000-0002-0319-976X (MDPI, 2021)
Horizontal bar rack bypass systems (HBR-BS) are characterized by a horizontal bar rack (HBR) with narrow clear bar spacing of 10–20 mm and an adjacent bypass (BS) to efficiently protect and guide downstream moving fish at water intakes. The small bar spacing may lead to operational challenges, such as clogging and high head losses. This study investigated whether combining an HBR with a low-voltage electric field (e-HBR) allows one to increase the clear bar spacing while maintaining a high standard of fish protection and guidance efficiency. To this end, an HBR-BS with 20 mm bar spacing and an e-HBR-BS with 20 and 51 mm bar spacing were tested with spirlin (Alburnoides bipunctatus) and European eel (Anguilla anguilla) in a laboratory flume. The racks were electrified with 38 V pulsed direct current. The protection efficiency of the e-HBR with 51 mm was 96% for spirlin and 86% for eels, which are similar results to those of the HBR with 20 mm. Some eels passed through the e-HBR, but only when they were parallel to the rack. Fish injuries of variable severeness due to the electrification were observed. The results highlight the potential of hybrid barriers for the protection of downstream moving fish. However, fish injuries due to electricity may occur; and reporting applied voltage, electrode geometry, resulting electric field strength and the pulse pattern of the electrified rack setup is necessary to ensure comparability among studies and to avoid injuries. ISSN:2073-4441